2015
DOI: 10.1002/jnr.23562
|View full text |Cite
|
Sign up to set email alerts
|

Calbindin‐D28Kis increased in the ventral horn of spinal cord by neuroprotective factors for motor neurons

Abstract: Slow glutamate-mediated neuronal degeneration is implicated in the pathophysiology of motor neuron diseases such as amyotrophic lateral sclerosis (ALS). The calcium-binding proteins calbindin-D28K and parvalbumin have been reported to protect neurons against excitotoxic insults. Expression of calbindin-D28K is low in adult human motor neurons, and vulnerable motor neurons additionally may lack parvalbumin. Thus, it has been speculated that the lack of calcium-binding proteins may, in part, be responsible for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…We have defined these two new types of neurons as MNs based on the facts that: (1) they co-express MN hallmark genes Mnx1, Chat, and Slc18a3 (VAChT); and (2) both types extend their axons from the spinal cord to peripherals. Although Calb1 is a salient marker for V1 subtype Renshaw cells 86 , the presence of a small number of Calb1 + MNs among adult spinal MNs has been reported previously 87,88 . In those studies, it was hypothesized that MNs are protected from glutamate-induced and calcium-mediated excitotoxicity via increased Calb1 expression.…”
Section: Exploring the Diversity Of Spinal Mnsmentioning
confidence: 88%
“…We have defined these two new types of neurons as MNs based on the facts that: (1) they co-express MN hallmark genes Mnx1, Chat, and Slc18a3 (VAChT); and (2) both types extend their axons from the spinal cord to peripherals. Although Calb1 is a salient marker for V1 subtype Renshaw cells 86 , the presence of a small number of Calb1 + MNs among adult spinal MNs has been reported previously 87,88 . In those studies, it was hypothesized that MNs are protected from glutamate-induced and calcium-mediated excitotoxicity via increased Calb1 expression.…”
Section: Exploring the Diversity Of Spinal Mnsmentioning
confidence: 88%
“…Previous reports have suggested that motor neurons are vulnerable in ALS because they are larger than other cells; require large amounts of energy to maintain homeostatic ionic gradients and generate action potentials; are easily overloaded [ 36 ]; and have a lower buffering capacity for glutamate-triggered calcium ion influx [ 37 ], decreased expression of calcium-binding proteins such as CalbindinD28K and parvalbumin [ 38 , 39 ], and decreased expression of GABAA receptor α1, which is involved in inhibitory synaptic transmission [ 40 , 41 ]. TDP-43 mislocalization from the nucleus to the cytoplasm is more common in neurons than in other cells in ALS [ 42 ], and the half-life of mutant TDP-43 is longer than that of WT TDP-43 [ 5 ], suggesting that alterations in TDP-43 function may enhance motor neuron vulnerability in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the intensive CaBp immunoreactivity was identified in the frontal cortex, but PV and/or NPY, other GABAergic makers, immunoreactivity would be weak on the contrary. CaBp is a marker of GABAergic neurons; however, this protein also has a neuroprotective function against neurodegeneration and ischemia (Greene et al, 2001; Iritani et al, 2001; Freimann et al, 2010; Spruill and Kuncl, 2015). In case of there being an ABCA13 deficit in the cortex, the neurons might induce neuroprotective mediators.…”
Section: Discussionmentioning
confidence: 99%